Si wire array waveguide grating with parallel star coupler configuration fabricated by ArF excimer immersion lithography. Issue 6 (1st March 2013) - Okayama, H.; Shimura, D.; Takahashi, H.; Seki, M.; Toyama, M.; Sano, T.; Koshino, K.; Yokoyama, N.; Ohtsuka, M.; Sugiyama, A.; Ishitsuka, S.; Tsuchizawa, T.; et al.
Abstract : An Si wire array waveguide grating wavelength demultiplexer fabricated using immersion ArF lithography is reported. The tilt directions of the input and output star couplers are aligned in the same direction to avoid phase error generated at the curved waveguides. A 16 channel device with 200 GHz wavelength spacing was fabricated.